Improving speed training of judoists with the help of circular training - Tangriev, A. J. (European Journal of Research and Reflection in Educational Sciences, 2019)
The article describes special exercises that are involved in technical exercises to perform exercises in a circular manner. A new program of complex exercises has been created that adapts judokas to the conditions of the competition.